Supplementation with Silk Amino Acids improves physiological parameters defining stamina in elite fin-swimmers - Zubrzycki, I. Z.; Ossowski, Z.; Przybylski, S.; Wiacek, M.; Clarke, A.; Trabka, B. (Journal of the International Society of Sports Nutrition, 2014)
Background: Previous animal study has shown that supplementation with silk amino acid hydrolysate (SAA) increase stamina in mice. The presented study was the first formal evaluation of the influence of SAA supplementation on parameters defining physiological fitness level in humans. Methods: It was a randomized controlled trial with a parallel-group design on elite male fin-swimmers. The experimental group was supplemented with 500 mg of SAA per kg of body mass, dissolved in 250 ml of a Carborade Drink ; the control group with Carborade Drink alone; 3 times a day, 30 minutes prior to the training session.ResultsChanges discerned in the experimental group were more pronounced than those observed in the control group. For example, the change in the serum lactic acid concentration observed in the experimental group was sevenfold less than in the control group [21.8 vs. -3.7 L% for the control and experimental groups, respectively]. An analysis of a lactate profile as a function of a maximal swimming velocity exposed a statistically significant positive shift in the swimming velocity of 0.05 m/s, at the lactate concentration of 4 mmol/L in the experimental group. There was also a positive, although statistically insignificant, increase of 2.6 L% in serum testosterone levels in the experimental group. Conclusions: This study showed that a 12-day SAA supplementation combined with an extensive and rigorous training schedule was sufficient to increase an aerobic stamina. However, this phenomenon was associated with an augmented level of muscular damage (an increased level of creatine phosphokinase in the experimental group).